2015
DOI: 10.1016/j.jaci.2014.07.065
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and infant exposure to acetaminophen and ibuprofen and the risk for wheeze and asthma in children

Abstract: Background Several studies have reported an association between use of over-the-counter antipyretics during pregnancy or infancy and increased asthma risk. An important potential limitation of these observational studies is confounding by indication. Objectives We investigated the association of antipyretic intake, 1) during pregnancy and 2) during the first year of life (infancy), with asthma-related outcomes, before and after controlling for early life respiratory infections. Methods We included 1490 mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 32 publications
(32 reference statements)
3
83
0
2
Order By: Relevance
“…In the analysis by Magnus et al ,23 relative risks of the association between asthma and paracetamol were 1.17 for prenatal exposure only, 1.27 for postnatal exposure only and 1.26 for both exposures. Moreover, another earlier study examining the association between cumulative (prenatal and postnatal) exposure to paracetamol and asthma development reported a positive association with adjusted OR 1.32% and 95% CI 1.06 to 1.65 18. Our findings are also largely in accordance with results summarised in a previous meta-analysis focusing on the association between asthma and paracetamol exposure in different periods of child development 25 26.…”
Section: Discussionsupporting
confidence: 92%
“…In the analysis by Magnus et al ,23 relative risks of the association between asthma and paracetamol were 1.17 for prenatal exposure only, 1.27 for postnatal exposure only and 1.26 for both exposures. Moreover, another earlier study examining the association between cumulative (prenatal and postnatal) exposure to paracetamol and asthma development reported a positive association with adjusted OR 1.32% and 95% CI 1.06 to 1.65 18. Our findings are also largely in accordance with results summarised in a previous meta-analysis focusing on the association between asthma and paracetamol exposure in different periods of child development 25 26.…”
Section: Discussionsupporting
confidence: 92%
“…The majority of birth cohort studies that have investigated this association have confirmed a positive relation, 4 including this latest study, which also showed that ibuprofen use in pregnancy was not a risk factor. 6 Sordillo et al 6 rightly point out that detailed information on indications for taking acetaminophen during pregnancy has been lacking from these studies, raising the theoretical possibility of confounding by indication. However, the association between prenatal acetaminophen exposure and asthma has been shown to be robust to adjustment for maternal asthma, migraine, and infections and antibiotic use in pregnancy.…”
mentioning
confidence: 99%
“…For several years, it has been known that acetaminophen (paracetamol) in pregnancy and early childhood is associated with a significantly increased risk of the child developing asthma. This was confirmed in 2 studies 11,12 published in 2015 that also adjusted for respiratory infections, under the assumption that if the acetaminophen was taken to treat respiratory infection and fever, then the infection itself might explain the increased risk. What these studies showed was that both mothers who took acetaminophen during early pregnancy and in-fants who took acetaminophen were at significantly increased risk of developing asthma and that this risk was mitigated but not abolished when respiratory tract infections were accounted for.…”
Section: Asthma In Pregnancymentioning
confidence: 83%
“…What these studies showed was that both mothers who took acetaminophen during early pregnancy and in-fants who took acetaminophen were at significantly increased risk of developing asthma and that this risk was mitigated but not abolished when respiratory tract infections were accounted for. 11,12 The teratogenicity risk of asthma medications to the developing fetus was addressed in 2 studies. The EXPECT study 13 evaluated the risk of omalizumab (Xolair) in pregnancy, evaluating 191 pregnant women who were exposed to omalizumab during their first trimester.…”
Section: Asthma In Pregnancymentioning
confidence: 99%